THE RESURRECTION OF THE PEOPLE’S ECONOMY A LITERATURE STUDY OF THE PHILANTHROPIC MOVEMENT OF HAJJ SAMANHUDI - Dedie Adhy Aksa; M. Irsyad Albarru (Edusoshum : Journal of Islamic Education and Social Humanities, 2022)
The purpose of this study was to determine the rise of the people's economic power through the moral philosophy of the philanthropic movement of Haji Samanhudi in his role as a child of the nation in the national movement from 1905 to 1916. The method used is the study of literature to reveal historical facts about the role of H. Samanhudi in the Sarekat Dagang Islam. To analyze these facts, the approach that is often used in historical research is used, namely the historical approach, the sociological approach to religion and the political approach. Through primary sources from newspapers and archives, while reference books and previous research as secondary sources. The data collected were analyzed and presented in the form of descriptive writing. Several results of literature studies state that the values ​​of Haji Samanhudi's philanthropic movement are evidenced by the first, high moral concern for indigenous small traders. Second, explore the value of the practice of trading monopoly and reviving the Islamic trading economy among the indigenous people. Third, the role of building a work ethic and enthusiasm for the indigenous people to be literate in the political, economic, religious and social fields.